2005
DOI: 10.1136/vr.156.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Survival and infectivity of porcine reproductive and respiratory syndrome virus in swine lagoon effluent

Abstract: PORCINE reproductive and respiratory syndrome virus (PRRSV) is an enveloped RNA virus that is both heat and pH labile. It is readily inactivated by drying or following contact with a broad range of disinfectants (Benfield and others 1992, Bloemraad and others 1994). In addition, PRRSV survives for extended periods when frozen or if in a moist environment (Benfield and others 1992, Bloemraad and others 1994, Pirtle and Beran 1996. In a study by Pirtle and Beran (1996), a standard concentration of PRRSV (2 x 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…However, several other reports do not support this hypothesis. For example, a previous study reported that PRRS was unlikely to be transmitted via contaminated lagoon effluent (Dee et al., 2005), and infectivity of PRRS virus for ducks is still controversial (Zimmerman et al., 1997; Trincado et al., 2004). Thus, the interaction between water green crop and ducks on farms needs to be interpreted cautiously until further information about some of the key parameters is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…However, several other reports do not support this hypothesis. For example, a previous study reported that PRRS was unlikely to be transmitted via contaminated lagoon effluent (Dee et al., 2005), and infectivity of PRRS virus for ducks is still controversial (Zimmerman et al., 1997; Trincado et al., 2004). Thus, the interaction between water green crop and ducks on farms needs to be interpreted cautiously until further information about some of the key parameters is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Because, the duration of Δs varies as a function of the pathogen of interest (Davies et al, ; Dee, Deen, Burns, Douthit, & Pijoan, ; Dee, Martinez, & Clanton, ; Dee, Torremorell, Thompson, Deen, & Pijoan, ; Linhares, Torremorell, Joo, & Morrison, ; Lowe et al, ; Olesen et al, ; Weesendorp, Stegeman, & Loeffen, ; Zimmerman et al, ) and as a function of the intensity of the cleaning activities carried out within the pig industry (Dee, Deen, et al, ; Dee, Torremorell, et al, ), we tested the impact of sharing PHC vehicles by considering various scenarios of Δs, notably Δs < 1, Δs = 1, Δs = 7 and Δs = 28 days. In total, 520 multilayer networks, which involved 1,040 single‐layer networks, were constructed and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…PRRS virus can be excreted from host species (pigs only) in aerosol, urine, semen, nasal secretions or saliva . Viable virus has also been detected in serum and has been shown to survive for several days in manure and effluent from piggeries. It can also be isolated from muscle of pigs at slaughter, and houseflies and mosquitoes ( Aedes spp.)…”
Section: Discussionmentioning
confidence: 99%